2022
DOI: 10.1128/jmbe.00346-21
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Yourself as a Scientist: Increasing Science Identity Using Professional Development Modules Designed for Undergraduate Students

Abstract: As educators, we should not assume that students are progressing toward intended STEM careers simply because they have persisted and received a STEM degree. In addition to learning biology content and scientific skills, students need guidance in making optimal career choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
3
14
0
1
Order By: Relevance
“…This finding suggests that an institutional intervention can influence science identity among Latinx college students. Similarly, McCartney et al (2022) found an increase in science identity in biology undergraduate students through a semester-long professional development intervention.…”
Section: Science Identity Development In Collegementioning
confidence: 89%
See 1 more Smart Citation
“…This finding suggests that an institutional intervention can influence science identity among Latinx college students. Similarly, McCartney et al (2022) found an increase in science identity in biology undergraduate students through a semester-long professional development intervention.…”
Section: Science Identity Development In Collegementioning
confidence: 89%
“…This finding suggests that an institutional intervention can influence science identity among Latinx college students. Similarly, McCartney et al (2022) found an increase in science identity in biology undergraduate students through a semester‐long professional development intervention. The current study extends prior research by examining the qualitative ways in which science identity changes over time for Latinx students when they receive institutional support via involvement in a culturally affirming URE.…”
Section: Introductionmentioning
confidence: 92%
“…Students perceive fewer benefits from office hours than instructors do, and some students hold negative perceptions of office hours. Increased efforts to explain the goals, benefits, and expectations of office hours may make students more comfortable and more likely to attend office hours Similarly, instructors may wish to consider ways to facilitate discussing some of these topics in office hours, such as career development and study skills, which can be valuable for students’ academic and professional development ( Durkin and Main, 2002 ; McCartney et al. , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan peta kompetensi yang telah ditentukan dalam penelitian ini, maka dibuat kerangka kerja modul yang dapat menggambarkan secara lengkap isi modul dan urutan penyajiannya. Modul harus dikembangkan untuk meningkatkan kepercayaan diri peserta didik terhadap pembelajaran dan pemahaman mereka terhadap materi Biologi (McCartney et al, 2022). Kemudian ditentukan langkah-langkah sistematik dari modul yang akan ditulis, pada langkah ini ditetapkan urutan strategis penyajian materi dan jenis ilustrasi yang akan digunakan.…”
Section: Hasil Dan Pembahasanunclassified